Structural characterization and anti-inflammatory activity of a novel polysaccharide PKP2-1 from Polygonatum kingianum - Wang, Zhen; Liu, Hui; Fu, Ranze; Ou, Jinmei; Wang, Bin (Frontiers in Nutrition, 2023)
Introduction This study aimed to investigate the structure characterization and antiinflammatory activity of a novel polysaccharide, PKP2-1, from the rhizomes of Polygonatum kingianum Coll. and Hemsl. Methods We isolated a novel polysaccharide, PKP2-1, from the rhizomes of Polygonatum kingianum Coll. and Hemsl. for the first time, which was then successively purified through hot-water extraction, 80% alcohol precipitation, anion exchange and gel permeation chromatography. The in vitro anti-inflammatory activity of PKP2-1 in MH7A cells was assessed using a CCK-8 kit assay. Results Monosaccharide composition assay revealed that PKP2-1 was mainly composed of glucose, galactose, mannose, and glucuronic acid at an approximate molar ratio of 6:2:2:1. It had a molecular weight of approximately 17.34 kDa. Structural investigation revealed that the backbone of PKP2-1 consisted of (→2, 3)-α-D-Galp(4→, →2)-α-D-Manp(3→, →2)-β-D-Glcp(4→) and α-D-Glcp(3→) residues with side chains (→2)-β-D-Glcp(4→, →1)-α-D-Galp(4→) and α-D-Glcp(3→) branches located at O-3 position of (→2, 3)-α-D-Galp(4→). The in vitro anti-inflammatory activity of PKP2-1 in MH7A cells revealed that PKP2-1 could reduce the expression of IL-11β and IL-6, increase the expression of IL-10 and induce apoptosis of synovial fibroblasts. Conclusion The PKP2-1 could inhibit MH7A cell growth and potentially be exploited as an anti-inflammatory agent.